(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Soybean is one important crop and infection by several fungal diseases. Root rot disease is a major impendence to global agriculture, decreasing crop production. This disease can wipe out entire fields depending on the environmental condition and causal agent. Root and stem lesions can progress to dark black lesions, stunting, and death. Root rots disease of soybean plants is caused by F. oxysporum. Current management strategies for pathogens include the use of pesticide seed treatment, crop rotation, seed selection, and fertile fields.